Old songs, new perspectives. Imagery in Latin American political songs (Revista Argentina de Musicología, 2026)
The broad and diffuse field of “political song” is often identified, in the Latin American context, with the equally vast concept of “nueva canción” (new song); however, the overlap between the two is only partial. Not all the works that comprise the Nueva Canción repertoire in Latin America have an explicitly political character, nor, conversely, does Nueva Canción encompass the entire spectrum of genres, traditions, and movements of politically charged song that traversed the subcontinent before, during, and after the great Nueva Canción era. The cases studied in this dossier span four decades, from the 1950s to the 1980s. The temporal distance that separates us from the phenomenon's heyday has translated, over the years, into a progressively more articulated and critical perspective, one that has moved beyond the predominantly testimonial character of the early literature. The topic now boasts an extensive and still-growing body of research, developed from diverse academic perspectives, aimed at illuminating previously scarcely explored geographical areas or thematic dimensions.
Keywords: Introduction